Bioavailability and effect of α-Fe2O3 nanoparticles on growth, fatty acid composition and morphological indices of Chlorella vulgaris. (November 2021) - Bibi, Muhammadi; Zhu, Xinyu; Munir, Mubashrah; Angelidaki, Irini
Abstract: The wide application of α-Fe2 O3 nanoparticles (NPs) in different fields has resulted in release and accumulation of these materials into the aquatic ecosystem. Therefore, it is important to understand the potential impact of these NPs on aquatic organisms especially primary producers i.e., microalgae. Present study aimed to investigate the bioavailability and the effect of α-Fe2 O3 NPs on growth of iron deprived cells of Chlorella vulgaris . Results showed that α-Fe2 O3 NPs are not available as iron source to support the growth of C. vulgaris . Moreover，α-Fe2 O3 NPs induced stress condition to C. vulgaris, which were reflected in its growth rates, total lipid contents, fatty acid profile and cell morphology. Specifically, low concentrations of α-Fe2 O3 NPs (0.1, 0.5, 2.5, 5, 10 mg/L) showed similar growth profile and total lipid contents at both exponential and stationary growth phases. At 50 and 100 mg/L α-Fe2 O3 NPs concentrations biomass reduced by 41.2% and 83.7% whereas total lipid contents increased by 39.7% and 25.5% respectively at exponential growth phase along with reduction in fatty acids. The results illustrated novel insights into the microalgal interaction with nanoparticles, providing fundamental knowledge for the development of future microalgae ecology and cultivation technology. Graphical abstract: Image 1 Highlights: α-Fe2 O3 NPs are not available for micronutrients supply for C. vulgaris growth. α-Fe2 O3 NPs imposed toxicity on C. vulgaris cell growth. Spiking of 50 and 100 mg/L α-Fe2 O3 NPs inhibit microalgae growth. α-Fe2 O3 NPs increased total lipid contents whilst fatty acid contents decreased. α-Fe2 O3 NPs induced morphological deformation and formation of EPS.